Water Relations and Low-Temperature Acclimation for Cactus Species Varying in Freezing Tolerance. - Goldstein, G. (1994)
Opuntia ficus-indica and Opuntia streptacantha are widely cultivated cacti that can tolerate temperatures no lower than -10[deg]C, whereas Opuntia humifusa, which is native to southern Canada and the eastern United States, can tolerate -24[deg]C. As day/night air temperatures were decreased from 30/20 to 10/0[deg]C, the osmotic pressure increased 0.10 MPa for O. ficus-indica and O. streptacantha but 0.38 MPa for O. humifusa. The increases in osmotic pressures were due mostly to the synthesis of fructose, glucose, and sucrose. In addition, O. humifusa produced a substantial amount of mannitol during exposure to low temperatures. Substantial accumulation of sugars and mannitol in cells of O. humifusa may help prevent intracellular freeze dehydration and ice formation as well as provide noncolligative protection to its membranes. Mucilage was slightly higher in all three species at the lower temperatures. Extracellular nucleation of ice occurred closer to the equilibrium freezing temperature for plants at 10/0[deg]C compared with 30/20[deg]C, which could make the cellular dehydration more gradual and, thus, less damaging. Results from nuclear magnetic resonance indicated a restricted mobility of intracellular water at the lower temperatures, especially for O. humifusa, which is consistent with its lower water content and higher levels of low molecular weight solutes.